Diabetic foot ulcer management with TLC-NOSF (Technology Lipido-colloid Nano-oligosaccharide Factor) wound dressings. Issue 4 (2021) - Long, Zhong; Jun, Wang; Shijun, Zhu; Don, Jiang; Xinzhao, Fan; Galea, Emilio
No abstract available